If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+6=51+3x
We move all terms to the left:
8x+6-(51+3x)=0
We add all the numbers together, and all the variables
8x-(3x+51)+6=0
We get rid of parentheses
8x-3x-51+6=0
We add all the numbers together, and all the variables
5x-45=0
We move all terms containing x to the left, all other terms to the right
5x=45
x=45/5
x=9
| 1+12x-8x+3=29 | | 5/95=x/208000 | | -7+u=5 | | 4t+5=-36 | | 2x+10+7x=-8 | | 28=v/4-12 | | v/5+17=38 | | 107-y=186 | | 8x+3x=3x+18 | | 27=-w+160 | | 8(x–3)=96 | | 6x+3=8x+37 | | 2) 8(x–3)=96 | | 263=-w+170 | | -(5y+5)-(-4y-8)=3 | | 2m-2m+3m=12 | | 8x–24=96 | | j+8=9 | | 8r-10r=14 | | X2-14x+49=0 | | 216-u=18 | | 13q-6q-9q=10 | | 71=3w+17 | | 3x=(3x+1) | | 13c-8c-1=19 | | 7(x−5)+31=7x−4 | | x+x+x+x+x+x+x+x+x+x+x+x=12 | | -81=-15x | | 6=(a+8) | | 2(4x-1)5(x-2)=6(2x+1) | | 14(x−2)=7+4x | | 7h-6h+6h+2=16 |